Collaborative Governance in Tackling Prostitution in Pemalang Regency - Tobirin Tobirin; Abdul Aziz Nasihuddin; Kadar Pamuji (Faculty of Law, Universitas Jenderal Soedirman, 2022)
This article is driven by the complexity of handling prostitution, from economic issues, conflicts of interest, poor communication coordination, to the absence of collaboration between stakeholders. This study aimed to analyze the implementation and obstacles of collaborative governance in dealing with prostitution in Pemalang Regency. A social-juridical research methodology through the combination of doctrinal-normative legal research and social as well as social science approaches was selected for this study, while data collection were obtained through focus group discussions and secondary data. The study results showed that the implementation of collaborative governance in handling prostitution in Pemalang Regency has not been optimal, with ineffective communication identified between stakeholders. In addition, the barriers to the collaborative process include conflicts of interest in the handling of prostitution issues that give rise to differing perceptions among the health service providers, security forces, and religious leaders; ineffective institutional design; and the reliance to the deparment in charge of handling public order. The lack of shared commitment to address prostitution issue in a planned and measurable manner in adherence to local regulations remains a challenge to be resolved.Keywords: barriers, collaborative, handling, prostitution.